Relationship between Mildly Elevated NT-proBNP Levels and Heart Failure Stages in the Elderly - Rana A. Hallak; Ahmed Alakedi; Mona Kardus; Ebtihal Al Amoudi; Ameerah Munassar; Mary Jaison; Hussein Zayed; Mohammed Jabal; Arwa Al Shatiri; Fahad Al Mubarak; Adel Saad; Rama Sarraj; et al. (Dr. Sulaiman Al Habib Medical Journal)
Background: Heart failure (HF) is a growing health concern among the elderly. Although NT-proBNP is a valuable biomarker for diagnosing HF, its levels are not easy to interpret in older subjects because of age-related increases. Previous data indicates that NT-proBNP levels above 450.0 pg/mL in patients aged 75 and older may indicate heart failure. This study aims to assess the significance of mildly increased NT-proBNP levels in individuals aged 75 and older, examining their correlation to echocardiographic results, associated risk factors, and clinical symptoms. The retrospective cohort included 400 elderly individuals with NT-proBNP levels between 450 and 1000 pg/ml, who sought treatment at Dr. Sulaiman Alhabib Group of Hospitals (HMG), Riyadh during the period from January 2021 to December 2022. They were classified according to the American College of Cardiology/American Heart Association (ACC/AHA) guidelines. Those with HF (ACC/AHA stage C) exhibited significantly higher NT-proBNP levels than those with pre-HF (stage B) (824.53 ± 112.56 pg/mL vs. 684 ± 160.73 pg/mL, P < 0.001). A cut-off value of >682.6 pg/mL offered 91.10% sensitivity and 54.72% specificity for HF diagnosis. Additionally, structural heart disease was more common in the HF group (76.7% vs. 53.9%, P < 0.001). Gender, cardiac symptoms, and other risk factors were observed to be significantly linked with NT-proBNP levels in multiple linear regression analysis. Objectives: This study aims to assess the significance of mildly increased NT-proBNP levels in individuals aged 75 and older, examining their correlation to echocardiographic results, associated risk factors, and clinical symptoms. Methods: A retrospective cohort study was conducted on 400 elderly individuals with NT-proBNP levels between 450 and 1000 pg/mL, treated at Dr. Sulaiman Alhabib Group of Hospitals, Riyadh, from January 2021 to December 2022. Patients were classified by ACC/AHA HF stages and analyzed for biomarker levels, echocardiographic findings, and clinical characteristics. The exclusion criteria encompassed patients whose dyspnea and fatigue were attributed to non-cardiac causes, such as pulmonary conditions, anemia, thyroid disorders, or other systemic illnesses. Results: Patients with HF (Stage C) exhibited significantly higher NT-proBNP levels than those with pre-HF (Stage B) (824.53 ± 112.56 pg/mL vs. 684 ± 160.73 pg/mL, P < 0.001). A cut-off value of >682.6 pg/mL provided 91.10% sensitivity and 54.72% specificity for HF diagnosis. Structural heart disease was more common in the HF group (76.7% vs. 53.9%, P < 0.001), and multiple risk factors were significantly associated with NT-proBNP levels. Conclusions: Mildly elevated NT-proBNP levels could indicate HF in elderly individuals, but careful interpretation is advised in conjunction with echocardiography and clinical symptoms. Further research is needed to establish age-specific reference ranges for NT-proBNP in older populations.